2016
DOI: 10.1177/0971721816661785
|View full text |Cite
|
Sign up to set email alerts
|

The Factors Affecting Basic Research Performance Funded by Government: ‘Creative Research Program’ Case in South Korea

Abstract: This study examines factors affecting the performance of basic research in South Korea. Creative Research Program (CRP), which is one of the major basic research programmes, is a study target. The survey of N = 120 researchers from universities and research institutes was conducted in 2010. Basic research performance which is the dependent variable was measured by subjective survey questions. The data were analysed using factor analysis and multiple regression. The result shows that leadership is the most impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Development orientation towards research university (RO&S1) [2,5,6] Establishing a set of plans and strategies to boost research activities (RO&S2) [9,11,36] Specific and widely communicated objectives (RO&S3) [7] Research strategies and objectives are built up in multiple dimensions (from top to bottom, from bottom to top, there is coordination between units and peer groups) (RO&S4) [1,7,17] 2 Decentralization (DC)…”
Section: Policy Towards Lecturers (Pl)mentioning
confidence: 99%
See 3 more Smart Citations
“…Development orientation towards research university (RO&S1) [2,5,6] Establishing a set of plans and strategies to boost research activities (RO&S2) [9,11,36] Specific and widely communicated objectives (RO&S3) [7] Research strategies and objectives are built up in multiple dimensions (from top to bottom, from bottom to top, there is coordination between units and peer groups) (RO&S4) [1,7,17] 2 Decentralization (DC)…”
Section: Policy Towards Lecturers (Pl)mentioning
confidence: 99%
“…Governance decisions are made on the basis of extensive stakeholder engagement, with emphasis on feedback systems and collaboration (DC1) [7,8] Governance activities promote academic independence, equality, communication, and connection among members (DC2) [1,17] The autonomy of institutions and lecturers (DC3) [9] Degree of lecturers' participation in the decision-making process about scientific research activities in their faculty/university (DC4) [17] 3 Leadership (LD)…”
Section: Policy Towards Lecturers (Pl)mentioning
confidence: 99%
See 2 more Smart Citations
“…Yulianto & Juwono (2021) and Ramezani et al, (2018) found that a weak research culture led to the lecturers' low research performance at universities. Furthermore, previous studies proved that leadership is a factor that significantly influenced research performance (Ryu, Hwang, & Choi, 2016). Based on numerous literature, one of the leadership models often studied related to research performance is academic leadership (Gerashchenko, 2021;Evans, 2014).…”
Section: Introductionmentioning
confidence: 99%